Preparation method and application of a new type of semiconductor single-walled carbon tube catalyst

By adopting the preparation method of a new semiconductor single-wall carbon tube catalyst, the problems of high production cost and low efficiency of single-wall carbon nanotubes are solved, and efficient and controllable production of single-wall carbon nanotubes is achieved, which is suitable for mass production.

CN119746929APending Publication Date: 2025-04-04WUXI NO 6 ELEMENT NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411964830.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art produces single-wall carbon nanotubes with high cost, complex preparation process and low catalyst efficiency, which limits their use in some applications.

Method used

The preparation method of a new semiconductor single-wall carbon tube catalyst is adopted. By placing a salt solution of the active component of the catalyst and the additive component, adding a reducing agent and a stabilizer, and passing through high-temperature heating reaction in the autoclave, a cage-shaped silsesquioxane-alloy anode catalyst is prepared for the production of single-wall carbon nanotubes.

Benefits of technology

The production efficiency of single-wall carbon nanotubes is significantly improved, cost is reduced, and the size controllable production of single-wall carbon nanotubes is realized. The catalyst preparation process is controllable and easy to implement, and is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746929A_ABST
    Figure CN119746929A_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a new type of semiconductor single-walled carbon tube catalyst, which utilizes the unique molecular structure of silsesquioxane to graft multiple reactive groups or metal atoms, improves the compatibility of different phases, increases the regularity and controllability of the molecular structure, and the end group contains multiple active reaction sites, connects multiple active reaction sites, and combines more active metals, which greatly improves the yield of carbon nanotubes. By controlling the proportion of metals in the active components of the catalyst, the diameter of the single-walled carbon nanotube is controlled, and the size-controlled production of single-walled carbon nanotubes is achieved. The catalyst preparation process in this method is controllable and easy to implement, the raw material source is wide, the price is low, the later single-walled carbon tube processing and instrument maintenance are simpler, and the mass production of single-walled carbon nanotubes can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor single-wall carbon nanotube catalysts, in particular to a preparation method and application of a new semiconductor single-wall carbon nanotube catalyst. Background Art

[0002] Single-walled carbon nanotubes are a special one-dimensional nanomaterial with radial dimensions of nanometers and axial dimensions of micrometers. The structure can be regarded as a one-dimensional cylindrical nanomaterial formed by rolling up two-dimensional graphene. The bonding method of carbon nanotubes is the same as that of graphene. The hybrid orbitals of carbon atoms are all sp2 hybridized, which makes carbon nanotubes have high strength and high modulus. The remaining p electrons of carbon atoms form a π electron cloud, and the conjugation effect is significant, which can show special electrochemical properties. Single-walled carbon nanotubes have a unique one-dimensional tubular structure and show unique excellence in electrical, thermal and mechanical properties. The current density of metallic single-walled carbon nanotubes is 2-3 orders of magnitude higher than that of copper, which has excellent conductive properties, reaching 10 9 A / cm 2 , is an ideal material for cables, etc. Its semiconductor single-walled carbon nanotubes are recognized as the most important candidate material for transistor channels in the post-Moore era, which is 3 orders of magnitude higher than silicon-based materials. Its thermal conductivity is 1 order of magnitude higher than copper, about 6600W / (m·K). Its tensile strength is two orders of magnitude higher than steel, about 100Gpa. These superb properties make single-walled carbon nanotubes have broad application prospects in catalysis, capacitors, absorbing materials, energy storage and materials.

[0003] At present, the preparation methods of single-walled carbon nanotubes include direct current arc method, electric explosion, fluidized bed CVD method, floating catalytic method and plasma arc method. However, the production of single-walled carbon nanotubes based on existing technologies has a complicated preparation process, requires high-quality raw materials and a very precise control system, and the production equipment is expensive. The catalyst efficiency is much lower than that of multi-walled carbon nanotubes, and the post-processing is complicated, which limits the use of single-walled carbon nanotubes in certain applications. Summary of the invention

[0004] In order to solve the problem of high cost of producing single-walled carbon nanotubes in the prior art, the present invention provides a method for preparing a new type of semiconductor single-walled carbon nanotube catalyst, which can improve the production efficiency of single-walled carbon nanotubes at a lower cost. At the same time, the application also discloses a method for preparing single-walled carbon nanotubes based on the new type of semiconductor single-walled carbon nanotube catalyst.

[0005] The technical solution of the present invention is as follows: a method for preparing a new type of semiconductor single-walled carbon tube catalyst, characterized in that it comprises the following steps: S1: preparing a catalyst active component salt solution and a catalyst promoter component salt solution, slowly dropping the catalyst promoter component salt solution into the catalyst active component salt solution, and stirring evenly to obtain a mixed solution A; The active components of the catalyst include: any one or more of iron salt, nickel salt and cobalt salt; The catalyst promoter is one or more of ammonium molybdate, ammonia water and ammonium nitrate; S2: adding a reducing agent to deionized water, adding a stabilizer to a buffer solution, and then mixing the two solutions to obtain a mixed solution B; The stabilizer includes: silsesquioxane; The reducing agent includes: one or more of formaldehyde, acetaldehyde and aniline; The buffer solution includes: an alkali solution with a pH of 8-9 or pure deionized water; S3: Mixed solution A is slowly added dropwise to mixed solution B, stirred evenly, and then transferred to a high-pressure reactor, heated at high temperature to react, and after crystallization, the product is taken out and placed in an oven for drying; after drying, the product is taken out and crushed to obtain particles below 60 mesh to obtain an anode catalyst; The anode catalyst is a cage-type silsesquioxane-alloy.

[0006] It is further characterized by: In step S1, the ratio of the catalyst active component salt solution to the catalyst promoter component salt solution is (1-2): 1; In step S2, the molar ratio of the silsesquioxane to the alloy in the catalyst active component is (1:6) to (1:8); The concentration of the catalyst active component salt solution is 0.2-0.5 mol / L; the concentration of the catalyst additive salt solution is 0.2-0.6 mol / L; The catalyst active components include: any one or more of potassium ferric chloride, ammonium ferric chloride, ferric nitrate, nickel sulfate, nickel acetate, nickel chloride, cobalt chloride, cobalt sulfate and cobalt nitrate; The raw material of silsesquioxane in the stabilizer includes: cage-type octaphenyl silsesquioxane or octavinyl silsesquioxane; When the buffer solution uses an alkali solution, the alkali solution is obtained by adding sodium hydroxide, ammonium bicarbonate or ammonium molybdate into deionized water and mixing them uniformly with ultrasound.

[0007] A method for preparing single-walled carbon nanotubes based on a novel semiconductor single-walled carbon nanotube catalyst, characterized in that it comprises the following steps: St1: The anode catalyst, carbon source and anode additive are fully mixed, a graphite binder is added, the mixture is placed in a mold and then dried in an oven to obtain an anode graphite rod with a catalyst effect; The anode auxiliary agent includes: one or more of yttrium trioxide, sulfur powder and sodium carbonate; St2: Install the anode graphite rod with catalyst on the anode of the arc generating device so that it faces the cathode graphite rod and maintains a preset distance; St3: Produces continuous arc discharge; St4: Collect the products deposited on the graphite cathode and the inner wall of the discharge chamber, purify, acid-wash and water-wash the products to obtain clean and high-purity single-walled carbon nanotubes.

[0008] It is further characterized by: It also includes the following steps: For the anode graphite rod, single-walled carbon nanotubes with different diameters are produced by adjusting the ratio of metal components in the catalyst active components; In step St1, when the solid C, the carbon source and the anode additive are mixed, the corresponding proportions are: silsesquioxane-alloy mass percentage: 1%-6%, yttrium trioxide mass percentage: 0.1-2%, sulfur powder mass percentage 0.1-2%, and the remainder is 99.99% pure graphite powder.

[0009] The present invention provides a method for preparing a new type of semiconductor single-walled carbon tube catalyst, which utilizes the unique molecular structure of silsesquioxane to graft multiple reactive groups or metal atoms, improves the compatibility of different phases, increases the regularity and controllability of the molecular structure, and the end group contains multiple active reaction sites, connects multiple active reaction sites, and combines more active metals, which greatly improves the yield of carbon nanotubes. By controlling the proportion of metals in the active components of the catalyst, the diameter of the single-walled carbon nanotube is controlled, and the size-controlled production of single-walled carbon nanotubes is achieved. The catalyst preparation process in this method is controllable and easy to implement, the raw material source is wide, the price is low, the later single-walled carbon tube processing and instrument maintenance are simpler, and the mass production of single-walled carbon nanotubes can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 Schematic diagram of the molecular structure of cage-type silsesquioxane; Figure 2 This is the electron microscope image of single-walled carbon nanotubes. DETAILED DESCRIPTION

[0011] In the anode catalyst prepared in this application, the characteristics of cage-type silsesquioxane molecules are used. As a hybrid material with organic-inorganic properties, the Si-O-Si structure in the compound structure of polyhedral silsesquioxane has good thermal stability and thermal oxygen stability. Due to the special structure, it can be combined with most substances in applications; Figure 1As shown, the caged silsesquioxane molecule can be grafted with one or more reactive groups or atoms; the non-reactive organic functional groups can be designed with different groups according to the properties of the polymer; other N, P, S or metal atoms can also be grafted to form the caged silsesquioxane-alloy in the present method. The three-dimensional structure of the caged silsesquioxane molecule contains a large number of organic end groups. The use of caged silsesquioxane with metal atoms can increase its reactivity. The multi-terminal active sites of silsesquioxane can coordinate with metal atoms to form metal organic / inorganic compounds. The catalytic activity of the supported catalyst can be improved by loading metal atoms, and the MO-Si structure formed by the active center bond of the metal atom. The combination of metal atoms and caged silsesquioxane improves the compatibility of different phases, increases the regularity and controllability of the molecular structure, and the end groups contain multiple active reaction sites, making its structure more diversified and more widely used.

[0012] The method for preparing a novel semiconductor single-walled carbon tube catalyst of the present invention comprises the following steps.

[0013] S1: preparing a catalyst active component salt solution and a catalyst auxiliary component salt solution, slowly dropping the catalyst auxiliary component salt solution into the catalyst active component salt solution, and stirring evenly to obtain a mixed solution A.

[0014] The active components of the catalyst include any one or more of iron salt, nickel salt and cobalt salt.

[0015] The catalyst auxiliary component is one or more of ammonium molybdate, ammonia water and ammonium nitrate.

[0016] The ratio of the catalyst active component salt solution to the catalyst auxiliary component salt solution is (1-2):1.

[0017] The concentration of the catalyst active component salt solution is 0.2-0.5 mol / L; the concentration of the catalyst auxiliary salt solution is 0.2-0.6 mol / L.

[0018] The active components of the catalyst include: any one or more of potassium ferric chloride, ammonium ferric chloride, ferric nitrate, nickel sulfate, nickel acetate, nickel chloride, cobalt chloride, cobalt sulfate and cobalt nitrate.

[0019] S2: Add the reducing agent into deionized water, add the stabilizer into the buffer solution and stir evenly, then mix the two solutions and perform ultrasonic homogenization to obtain a mixed solution B.

[0020] The stabilizer includes silsesquioxane; the raw material of the silsesquioxane in the stabilizer includes cage-type octaphenyl silsesquioxane or octavinyl silsesquioxane; the molar ratio of silsesquioxane to the metal in the catalyst active component is (1:6) to (1:8).

[0021] The reducing agent includes one or more of formaldehyde, acetaldehyde and aniline.

[0022] The buffer solution includes: an alkali solution with a pH value of 8-9 or pure deionized water; when the buffer solution uses the alkali solution, the alkali solution is obtained by adding sodium hydroxide, ammonium bicarbonate or ammonium molybdate into deionized water and uniformly mixing the mixture through ultrasonic mixing.

[0023] S3: Mixed solution A is slowly added dropwise to mixed solution B, and ultrasonically mixed for 20 minutes to obtain a white suspension. The white suspension is transferred to a high-pressure reactor and reacted at 180°C for 5 hours. It is heated at high temperature to react, and after crystallization, the product is taken out and placed in an oven at 80°C for drying; after drying, it is taken out and crushed and sieved, and solid particles below 60 mesh are taken to obtain an anode catalyst; the anode catalyst is a cage-type silsesquioxane (POSS)-alloy solid powder. This method uses a cage-type silsesquioxane-alloy below 60 mesh as a catalyst to ensure that the diameter of the generated single-walled carbon nanotubes is small enough.

[0024] Because when single-walled carbon nanotubes are generated based on the DC arc method, when the arc excites the anode carbon rod into vapor powder, the carbon particles grow into single-walled carbon nanotubes on the catalyst surface; the shape of the single-walled carbon nanotubes is similar to a hollow cylinder, and they are produced on the surface of metal particles in the catalyst. The diameter of the single-walled carbon nanotubes is positively correlated with the particle size of the metal atoms. The larger the particle size of the metal atoms, the larger the diameter of the single-walled carbon nanotubes. Therefore, among the three metal atoms of iron, nickel and cobalt, the particle sizes of iron and cobalt atoms are similar, and the particle size of nickel atoms is the smallest. The diameter of the single-walled carbon nanotubes grown on the surface of nickel atoms is smaller than that of the single-walled carbon nanotubes grown based on iron and cobalt atoms.

[0025] Therefore, when using this method to prepare a catalyst, in specific implementation, single-walled carbon nanotubes of different diameters can be produced by adjusting the proportion of iron, nickel and cobalt in the catalyst promoter. When the proportion of nickel and cobalt is too large, the average diameter of the generated single-walled carbon nanotubes is too large, and when the proportion of nickel and cobalt is too large, the average diameter of the generated single-walled carbon nanotubes is too small. The size of the single-walled carbon nanotubes can be controlled.

[0026] At the same time, the more metal atoms in the catalyst, the greater the yield of single-walled carbon nanotubes. Therefore, this method utilizes the unique molecular structure of cage-type silsesquioxane and its ability to graft multiple reactive groups or metal atoms, thereby improving the compatibility of different phases, increasing the regularity and controllability of the molecular structure, and the end group contains multiple active reaction sites, connecting multiple active reaction sites, and combining more active metals, which greatly improves the yield of carbon nanotubes. Among them, the yield of carbon nanotubes refers to the ratio of the mass of generated carbon to the mass of the catalyst.

[0027] A method for preparing single-walled carbon nanotubes based on a novel semiconductor single-walled carbon nanotube catalyst, characterized in that it comprises the following steps: St1: Fully mix the anode catalyst, carbon source and anode additive, add graphite binder, place in a mold and put in an oven to dry to obtain an anode graphite rod with catalyst effect. Among them, the graphite binder is one or more of high-temperature coal tar, epoxy resin and asphalt. The carbon source is carbon powder with a diameter of 200nm or a standard graphite rod suitable for electric arc furnace equipment.

[0028] In this embodiment, when solid C, a carbon source and an anode additive are mixed, the corresponding proportions of the components other than the anode additive are: silsesquioxane-alloy mass percentage: 1%-6%, and the remainder is graphite powder with a purity of 99.99%; wherein, the anode additive is one or more of yttrium trioxide, sulfur powder and sodium carbonate. Regardless of any one of them or any combination of them used, the corresponding mass percentage of each anode additive is 0.1-2%.

[0029] For example, if only sodium carbonate is used as an anode additive, then: the mass percentage of sodium carbonate is 0.1-2%, the mass percentage of silsesquioxane-alloy is 1%-6%, and the remainder is graphite powder with a purity of 99.99%.

[0030] If the components of the anode additive used include: yttrium trioxide and sulfur powder, then: yttrium trioxide mass percentage: 0.1-2%, sulfur powder mass percentage 0.1-2%, silsesquioxane-alloy mass percentage: 1%-6%, and the remainder is 99.99% pure graphite powder.

[0031] St2: Install the anode graphite rod with catalyst on the anode in the arc generating device so that it faces the cathode graphite rod and maintains a preset distance.

[0032] In this embodiment, single-walled carbon nanotubes are produced based on a direct current arc method using an anode graphite rod with a catalyst prepared in the present application.

[0033] The vacuum system is mainly composed of mechanical pumps, electric vacuum valves, vacuum pipes, and vacuum instruments. Its main function is to provide a vacuum environment for the reaction chamber. The arc generating device is composed of a low-voltage circuit and a reaction chamber. Under a certain atmosphere and pressure, the anode contacts the cathode to start an arc, and then a certain distance is maintained between the anode and the cathode to generate a continuous arc discharge. At the same time, the gas in the reaction chamber can be replaced by inert gas replenishment and vacuum operation, so that the gas environment in the chamber reaches a state close to pure inert gas or vacuum, providing a good environment for arc generation.

[0034] Based on the existing DC arc method technology, the constant pressure operation is automatically performed according to the set upper and lower pressure values, and the pressure of the reaction chamber is adjusted to reach the appropriate pressure state for arc reaction. In real time, the chiller can also be turned on and the circulating water is automatically turned on to ensure that the temperature of the reaction chamber will not be too high to cause danger.

[0035] St3: Produces continuous arc discharge.

[0036] During the arc discharge process, carbon atoms and the metal catalyst filled in the anode graphite rod evaporate, and the carbon atoms are reorganized under the action of multiple factors to form carbon nanomaterials, while products are deposited on the graphite cathode and the inner wall of the discharge chamber.

[0037] St4: Collect the products deposited on the graphite cathode and the inner wall of the discharge chamber, purify, acid-wash and water-wash the products to obtain clean and high-purity single-walled carbon nanotubes.

[0038] In the process of producing single-walled carbon nanotubes, the buffer gas is one or more of helium and argon, and the pressure of the buffer gas is 420mba-470mba. The reducing gas includes hydrogen. The discharge voltage ranges from 30-60V, and the discharge current ranges from 80-120A. Based on this method, continuous sampling can be carried out to produce single-walled carbon nanotubes intermittently.

[0039] In the process of preparing single-walled carbon nanotubes based on the direct current arc method, the single-walled carbon nanotubes can be grown in the reaction chamber to ensure relatively stable temperature and pressure during the reaction, making the growth environment of the single-walled carbon nanotubes more suitable. It can also ensure that the growing single-walled carbon nanotubes will not be affected by the subsequent impurities and amorphous carbon attached to the single-walled carbon nanotubes, thereby ensuring the purity of the product single-walled carbon nanotubes.

[0040] The novel arc method adopted in the present application is to prepare the anode catalyst of semiconductor single-walled carbon nanotubes. By preparing metal-based nanomaterials containing organic ligands, the controllable synthesis of single-walled carbon nanotubes can be achieved, which can solve the shortcomings of the current arc method for preparing single-walled carbon nanotubes, such as low yield, high ash content, high multi-walled tube content and uneven distribution of single-walled carbon nanotubes, and realize high-yield production of high-quality single-walled carbon nanotubes.

[0041] Compared with the traditional arc method catalyst, the single-walled carbon nanotube catalyst prepared by the present invention has adjustable performance and size, uniform distribution of active components, will not sinter after high-temperature treatment, has a short reaction time for a single catalyst, and is fully burned, and can maximize the use of the catalyst to produce single-walled carbon nanotubes. The diameter of the produced single-walled carbon nanotubes is distributed in the range of 1-3nm, and the tube diameter is uniform and evenly distributed. From the Raman spectrum test results, it can be seen that the single-walled carbon nanotubes generated by the catalyst have few defects and a high degree of graphitization. Specifically, Figure 2As shown, 100nm, 50nm and 10nm in the figure are electron microscope scales. The morphology and purity of the single-walled carbon nanotubes can be clearly seen at 100nm and 50nm, and the size of the single-walled carbon nanotubes can be seen in the electron microscope image with a scale of 10nm.

[0042] The novel ultrafine array carbon tube catalyst and the carbon nanotubes prepared therefrom of the present application are described below with reference to specific embodiments.

[0043] Embodiment 1: Potassium ferric chloride, nickel acetate and cobalt sulfate were stirred evenly in 100 mL of deionized water to prepare an active component solution with a concentration of 0.5 mol / L of iron, nickel and cobalt, respectively. Ammonium bicarbonate and ammonium molybdate were stirred evenly in 100 mL of deionized water at a mass ratio of 1:1.2 to prepare a catalyst auxiliary component salt solution with a molybdenum content of 0.8 mol / L. The catalyst auxiliary component salt solution was slowly added dropwise to the catalyst active component salt solution, and mixed solution A was obtained after stirring evenly.

[0044] Octavinylsilsesquioxane and formaldehyde were added to 500 mL of deionized water in sequence, stirred evenly, and ultrasonically mixed to obtain a mixed solution B with concentrations of the two substances of 0.02 mol / L and 0.5 mol / L.

[0045] Slowly drop the mixed solution A into the mixed solution B, mix them in a mass ratio of 1:1, and stir evenly to obtain a white suspension.

[0046] The white suspension was transferred to a high-pressure reactor, and a 1 cm thick aluminum sheet was added to promote the forward reaction and improve the reaction efficiency. The reaction was allowed to proceed at 180°C in an oil bath for 1 hour. During the crystallization process, the pressure relief device of the high-pressure reactor was opened to ensure that the entire reaction process was completed under a certain pressure condition until all the steam was discharged.

[0047] After crystallization, take out the product and place it in an oven at 80°C for drying. After drying, take out and crush, take particles below 60 mesh, and obtain solid powder. Take 1g of the above solid powder, 2.5g of 99.99% graphite powder with a diameter of 200nm, 0.2g of yttrium trioxide and 0.16g of sulfur powder, stir them evenly in a stirring machine, and add 0.2g of graphite binder, that is, high-temperature coal tar. Put the mixture into a cylindrical mold with a diameter of 1cm and a length of 15cm prepared in advance, press mold for 2h, put it in an oven, and dry it at 80°C for 1h to obtain a new type of arc method for preparing semiconductor single-walled carbon nanotube anode catalyst.

[0048] Preparation of single-walled carbon nanotubes: First, use a mechanical pump to extract the air in the reaction chamber through the air extraction port so that the air pressure in the reaction chamber reaches 2*10 -3pa, then helium is introduced into the reaction chamber to make its internal pressure reach 0.07MPa, a voltage is applied between the two electrodes to cause arc discharge, and then the voltage between the two graphite electrodes is adjusted to 80V to maintain the discharge current at 115A. During the arc discharge process, the cathode graphite rod is pushed forward because the anode is constantly consumed. The cathode electrode push speed is set to 20-25mm / min, and the rotation speed is set to 3r / min. During the arc discharge process, carbon atoms and metal catalysts filled in the anode graphite rod evaporate, and carbon atoms are reorganized to form carbon nanomaterials under the action of multiple factors, and products are deposited on the graphite cathode and the inner wall of the discharge chamber. The product is 8g, the yield of carbon nanotubes reaches 10 times, the conductivity is 9000S / m, the diameter of carbon nanotubes is 1-3nm, and the catalyst is qualified.

[0049] Comparative Example 1: Based on the conventional arc method catalyst phase, single-walled carbon nanotubes were generated based on the DC arc method.

[0050] After the graphite powder, Fe powder and sulfur powder with a purity of 99.99% are fully mixed in a molar ratio of 94%:5%:1%, 25wt% coal tar is added to the mixture and pressed into a rod to obtain the anode catalyst in the prior art; then the anode catalyst rod body is placed in a high-temperature furnace protected by nitrogen and treated at 1000°C for 3 hours to obtain the anode graphite rod. The anode graphite rod is placed in an arc chamber with 12KPa hydrogen and 18KPa argon gas facing the graphite cathode, and the discharge current between the positive and negative electrodes is controlled to be 90A~100A, the discharge voltage is 60V~70V, and the discharge time is 8 minutes, and finally 1g of semiconductor single-walled carbon nanotubes is obtained; the carbon nanotube yield is about 3 times.

[0051] The carbon nanotube yield in this application refers to the ratio of the mass of generated carbon to the mass of the catalyst. According to the nanotube yield, the anode catalyst in this application effectively increases the nanotube yield.

[0052] Comparative Example 2: Nickel acetate was stirred evenly in 100 mL of deionized water to prepare an active component solution with a nickel concentration of 0.5 mol / L; ammonium bicarbonate and ammonium molybdate were stirred evenly in 100 mL of deionized water at a mass ratio of 1:1.2 to prepare an auxiliary component salt solution with a molybdenum content of 0.8 mol / L. The auxiliary component salt solution was slowly added dropwise to the active component salt solution to obtain solution A.

[0053] Octavidinylsilsesquioxane and formaldehyde were added to 500 mL of deionized water in sequence, stirred evenly, and ultrasonically mixed to obtain an active component mixed solution B with concentrations of the two substances of 0.02 mol / L and 0.5 mol / L.

[0054] Slowly drop the mixed solution A into the mixed solution B, mix them in a mass ratio of 1:1, and stir evenly to obtain a white suspension.

[0055] The white suspension was transferred to a high-pressure reactor, and a 1-cm-thick aluminum sheet was added to promote the forward reaction and improve the reaction efficiency; it was reacted at 180°C in an oil bath for 1 hour. During the crystallization process, the pressure relief device of the high-pressure reactor was opened to ensure that the entire reaction process was completed under certain pressure conditions until all the steam was discharged.

[0056] After crystallization, take out the product and place it in an oven at 80°C for drying. After drying, take out and crush, take particles below 60 mesh, and obtain solid powder. Take 1g of the above solid powder, 2.5g of 99.99% graphite powder with a diameter of 200nm, 0.2g of yttrium trioxide and 0.16g of sulfur powder, stir evenly in a stirring machine, and add 0.2g of graphite binder, that is, high-temperature coal tar. Put the mixture into a cylindrical mold with a diameter of 1cm and a length of 15cm prepared in advance, press it for 2h, put it in an oven, and dry it at 80°C for 1h to obtain a new arc method for preparing semiconductor single-walled carbon nanotubes. The anode catalyst. The product is 4g, the yield of carbon nanotubes reaches 5 times, the conductivity is 7000S / m, and the diameter of carbon nanotubes is 1-4nm.

[0057] Comparative Example 2 also prepares anode catalysts based on the present method. However, compared with Example 1, the concentrations of iron, nickel and cobalt in the active component solution of Example 1 are 0.5 moL / L respectively; whereas in Comparative Example 2, the active component solution contains only nickel at a concentration of 0.5 moL / L.

[0058] In Example 1, the product is 8 g, the yield of carbon nanotubes reaches 10 times, the conductivity is 9000 S / m, and the diameter of the carbon nanotubes is 1 to 3 nm.

[0059] In Comparative Example 2, the product is 4 g, the yield of carbon nanotubes reaches 5 times, the conductivity is 7000 S / m, and the diameter of the carbon nanotubes is 1-2 nm.

[0060] It can be seen that as the metal content in the catalyst decreases, the yield of carbon nanotubes also decreases, from 10 times to 5 times. The average diameter of carbon nanotubes also decreases slightly.

[0061] Comparative Example 3: Potassium ferric chloride, nickel acetate and cobalt sulfate were stirred evenly in 100 mL of deionized water to prepare active component solutions with concentrations of iron, nickel and cobalt of 0.5 mol / L, 0.2 mol / L and 0.1 mol / L respectively; ammonium bicarbonate and ammonium molybdate were stirred evenly in 100 mL of deionized water at a mass ratio of 1:1.2 to prepare an auxiliary component salt solution with a molybdenum content of 0.8 mol / L. The auxiliary component salt solution was slowly added dropwise to the active component salt solution to obtain solution A.

[0062] Octavidinylsilsesquioxane and formaldehyde were added to 500 mL of deionized water in sequence, stirred evenly, and ultrasonically mixed to obtain an active component mixed solution B with concentrations of the two substances of 0.02 mol / L and 0.5 mol / L.

[0063] Slowly drop the mixed solution A into the mixed solution B, mix them in a mass ratio of 1:1, and stir evenly to obtain a white suspension.

[0064] The white suspension was transferred to a high-pressure reactor, and a 1-cm-thick aluminum sheet was added to promote the forward reaction and improve the reaction efficiency; it was reacted at 180°C in an oil bath for 1 hour. During the crystallization process, the pressure relief device of the high-pressure reactor was opened to ensure that the entire reaction process was completed under certain pressure conditions until all the steam was discharged.

[0065] After crystallization, take out the product and place it in an oven at 80°C for drying. After drying, take out and crush, take particles below 60 mesh, and obtain solid powder. Take 1g of the above solid powder, 2.5g of 99.99% graphite powder with a diameter of 200nm, 0.2g of yttrium trioxide and 0.16g of sulfur powder, stir them evenly in a stirring machine, and add 0.2g of graphite binder, that is, high-temperature coal tar. Put the mixture into a cylindrical mold with a diameter of 1cm and a length of 15cm prepared in advance, put it into an oven after compression molding for 2h, and dry it at 80°C for 1h to obtain a new arc method for preparing semiconductor single-walled carbon nanotubes. The anode catalyst. The product is 4g, the yield of carbon nanotubes reaches 7.1 times, the conductivity of carbon nanotubes is 6800S / m, and the diameter of carbon nanotubes is 1-5nm.

[0066] Comparative Example 3 is also based on the present method to prepare the anode catalyst, but compared with Example 1 and Comparative Example 2: In the active component solution of Example 1, the concentrations of iron, nickel and cobalt are 0.5 mol / L respectively; In Comparative Example 2, the active component solution contained only nickel at a concentration of 0.5 mol / L; In Comparative Example 3, the concentrations of iron, nickel and cobalt in the active component solution are 0.5 moL / L, 0.2 moL / L and 0.1 moL / L, respectively.

[0067] In Example 1, the product is 8 g, the yield of carbon nanotubes reaches 10 times, the conductivity is 9000 S / m, and the diameter of the carbon nanotubes is 1 to 3 nm.

[0068] In Comparative Example 2, the product is 4 g, the yield of carbon nanotubes reaches 5 times, the conductivity is 7000 S / m, and the diameter of the carbon nanotubes is 1-2 nm.

[0069] In Comparative Example 3, the product is 4 g, the carbon nanotube yield is 7.1 times, the conductivity is 6800 S / m, and the carbon nanotube diameter is 1 to 3 nm.

[0070] It can be seen that with the change of the total metal content in the catalyst: (0.5+0.5+0.5), (0.5+0.2+0.1), 0.5, the change of yield is: 10, 7.1, 5. The catalyst tube diameter of the single metal active component is the smallest, and there is no obvious difference in the catalyst tube diameter of the alloy active component.

[0071] After using the technical solution of the present invention, the active metal precursor is reduced by a reducing agent and then combined with the cage-type silsesquioxane POSS, and then the POSS-metal is bonded with carbon powder with a diameter of 200nm under the action of a graphite binder (high-temperature coal tar), and dried and calcined under high-temperature heating conditions to prepare an anode. A preparation method of cage-type silsesquioxane / metal (POSS-metal) and its application in the preparation of single-walled carbon nanotubes are also disclosed. The present application provides a novel arc method for preparing anode catalysts for semiconductor single-walled carbon nanotubes, which can significantly improve the yield and quality of single-walled carbon nanotubes. The core metal structure parameters of the catalyst can be precisely controlled, so that the single-walled carbon nanotubes prepared have the advantages of high purity and good tube diameter uniformity.

Claims

1. A method for preparing a new type of semiconductor single-walled carbon tube catalyst, characterized in that: It includes the following steps: S1: preparing a catalyst active component salt solution and a catalyst promoter component salt solution, slowly dropping the catalyst promoter component salt solution into the catalyst active component salt solution, and stirring evenly to obtain a mixed solution A; The active components of the catalyst include: any one or more of iron salt, nickel salt and cobalt salt; The catalyst promoter is one or more of ammonium molybdate, ammonia water and ammonium nitrate; S2: adding a reducing agent to deionized water, adding a stabilizer to a buffer solution, and then mixing the two solutions to obtain a mixed solution B; The stabilizer includes: silsesquioxane; The reducing agent includes: one or more of formaldehyde, acetaldehyde and aniline; The buffer solution includes: an alkali solution with a pH of 8-9 or pure deionized water; S3: Mixed solution A is slowly added dropwise to mixed solution B, stirred evenly, and then transferred to a high-pressure reactor, heated at high temperature to react, and after crystallization, the product is taken out and placed in an oven for drying; after drying, the product is taken out and crushed to obtain particles below 60 mesh to obtain an anode catalyst; The anode catalyst is a cage-type silsesquioxane-alloy.

2. The method for preparing a novel semiconductor single-walled carbon tube catalyst according to claim 1, characterized in that: In step S1, the ratio of the catalyst active component salt solution to the catalyst auxiliary component salt solution is (1-2):

1.

3. The method for preparing a novel semiconductor single-walled carbon tube catalyst according to claim 1, characterized in that: In step S2, the molar ratio of the silsesquioxane to the alloy in the catalyst active component is (1:6) to (1:8).

4. The method for preparing a novel semiconductor single-walled carbon tube catalyst according to claim 1, characterized in that: The concentration of the catalyst active component salt solution is 0.2-0.5 mol / L; the concentration of the catalyst additive salt solution is 0.2-0.6 mol / L.

5. The method for preparing a novel semiconductor single-walled carbon tube catalyst according to claim 1, characterized in that: The catalyst active components include: any one or more of potassium ferric chloride, ammonium ferric chloride, ferric nitrate, nickel sulfate, nickel acetate, nickel chloride, cobalt chloride, cobalt sulfate and cobalt nitrate.

6. The method for preparing a novel semiconductor single-walled carbon tube catalyst according to claim 1, characterized in that: The raw material of the silsesquioxane in the stabilizer includes: cage-type octaphenyl silsesquioxane or octavinyl silsesquioxane.

7. The method for preparing a novel semiconductor single-walled carbon tube catalyst according to claim 1, characterized in that: When the buffer solution uses an alkali solution, the alkali solution is obtained by adding sodium hydroxide, ammonium bicarbonate or ammonium molybdate into deionized water and mixing them uniformly with ultrasound.

8. A method for preparing single-walled carbon nanotubes based on a new type of semiconductor single-walled carbon nanotube catalyst, characterized in that: It includes the following steps: St1: The anode catalyst, carbon source and anode additive are fully mixed, a graphite binder is added, the mixture is placed in a mold and then dried in an oven to obtain an anode graphite rod with a catalyst effect; The anode auxiliary agent includes: one or more of yttrium trioxide, sulfur powder and sodium carbonate; St2: Install the anode graphite rod with catalyst on the anode of the arc generating device so that it faces the cathode graphite rod and maintains a preset distance; St3: Produces continuous arc discharge; St4: Collect the products deposited on the graphite cathode and the inner wall of the discharge chamber, purify, acid-wash and water-wash the products to obtain clean and high-purity single-walled carbon nanotubes.

9. The method for preparing single-walled carbon nanotubes based on a novel semiconductor single-walled carbon nanotube catalyst according to claim 8, characterized in that: It also includes the following steps: For the anode graphite rod, single-walled carbon nanotubes with different diameters are produced by adjusting the proportion of metal components in the catalyst active components.

10. The method for preparing single-walled carbon nanotubes based on a novel semiconductor single-walled carbon nanotube catalyst according to claim 8, characterized in that: In step St1, when the solid C, the carbon source and the anode additive are mixed, the corresponding proportions are: silsesquioxane-alloy mass percentage: 1%-6%, yttrium trioxide mass percentage: 0.1-2%, sulfur powder mass percentage 0.1-2%, and the remainder is 99.99% pure graphite powder.